Incomplete vertical root fracture associated with lateral compaction technique: a microscopic analysis - Chavez-Andrade, Gissele moraima [UNESP]; Andolfatto, Carolina [UNESP]; Salles, Loise Pedrosa [UNESP]; Cornélio, Ana Lívia Gomes [UNESP]; Faria, Gisele [UNESP]; Bonetti Filho, Idomeo [UNESP] (Editora Cubo, 2013)
Objective: This study evaluated the effects of root canal obturation employing lateral compaction technique and spreader load of 1.5 kg on the incidence of complete (CVRF) or incomplete vertical root fractures (IVRF). Material and Methods: Twenty-seven distal roots of extracted human mandibular molars were used. All root canals were prepared by biomechanical step-back technique and obturated by lateral compaction technique. The prepared roots were distributed into two groups: G1- experimental (n = 17) and G2- control (n = 10). During obturation, load of 1.5 kg was applied to a size # 30 finger spreader. Pre- and post-obturation images of the coronal portion of the roots were captured by inverted digital microscopy and analyzed by one trained examiner. Data were evaluated by Fisher’s test (p < 0.05) using GrapH Pad Prism 5.0. Results: No roots exhibited CVRF. All fractures observed before and after obturation were IVRF or “other defects”. In G2 (control group), there was no increase of IVRF number. Interestingly, G1 presented an increase in the IVRF number to 70.59% in the 12 teeth out of 17 teeth studied. The statistical analysis showed that the mean of IVRF increased significantly in G1 when compared to G2 (p < 0.05). Conclusion: The application of a 1.5 kg spreader load during lateral compaction technique does not produce complete vertical root fractures, but may produce incomplete fractures or “other defects”.

Objetivo: Este estudo avaliou os efeitos da obturação dos canais radiculares, empregando a técnica de condensação lateral com uma força do espaçador de 1,5 kg, na incidência de fraturas radiculares verticais completas (FRVC) ou incompletas (FRVI). Material e Métodos: Foram usadas 27 raízes distais de dentes molares mandibulares humanos extraídos. Todas as raízes foram instrumentadas por meio da técnica clássica ápice-coroa e obturadas pela técnica de condensação lateral. Após o preparo biomecânico, as raízes foram distribuídas em 2 grupos: G1- experimental (n = 17) e G2- controle (n = 10). Durante a obturação, uma força de 1,5 kg foi aplicada ao espaçador digital # 30. As imagens pré- e pós-obturação da superfície coronal das raízes foram capturadas por meio de um microscópio digital invertido e analisadas por um examinador treinado. Os dados obtidos foram avaliados por meio do teste de Fisher (p < 0,05) usando o programa GrapH Pad Prism 5.0. Resultados: Não foram detectadas FRVC. Todas as fraturas observadas antes e após a obturação foram FRVI ou “outros defeitos”. No G2 (grupo controle), não houve um aumento no número de FRVI. Curiosamente, G1 apresentou um aumento das FRVI em 70,59% (12/17 raízes). A análise estatística mostrou que a média de FRVI aumentou significativamente no G1 quando comparado ao G2 (p < 0,05). Conclusão: A aplicação de uma força de 1,5 kg ao espaçador durante a realização da técnica de condensação lateral não produz fraturas radiculares verticais completas, mas pode produzir fraturas incompletas ou “outros defeitos”.
Fratura radicular vertical incompleta associada com a técnica de condensação lateral: Análise microscópica
Keywords: Endodontics; Root canal obturation; Vertical root fracture; Endodontia; Fratura radicular vertical; Obturação do canal radicular